Vascular epiphyte biomass in a South Brazilian fragment of Atlantic Forest - PETEAN,MARISE P. (2018)
Abstract The present study aimed at sampling the biomass of vascular epiphytes within a protected area in South Brazilian Atlantic Forest. All tree specimens with diameter at breast height equal or greater than 4.8 cm were measured and divided into classes. In each class, 10% of tree specimens were randomly selected for epiphytic biomass measuring. Furthermore, we divided the phorophytes into five tree parts to analyze epiphytic biomass. We generated mathematical models to estimate epiphytic biomass in similar forest areas. We analyzed 55 phorophytes and found an estimated epiphytic biomass of 5.3 Mg/ha. Epiphytic biomass ranged from 0.02 to 135 kg and the lower values were found on small-sized phorophytes. Higher values of epiphytic biomass were found on phorophytes with diameter at breast height between 30 and 36.5 cm. The tree part with higher epiphytic biomass was the outer crown. The epiphytic biomass showed a high correlation with phorophyte diameter, according to the mathematical models. We selected two equations which presented the most similar values to the ones we measured. Our results corroborate that epiphytes play a very important role as to the biomass level within tropical forests.